Preparation method of special magnetic wear-resistant polyurethane lining material for iron ore sand mill

By covering the surface of magnetic ferrite nanoparticles with zirconia to form a core-shell structure, and introducing it into polyurethane materials, the problem of insufficient durability of traditional polyurethane materials in high wear, high impact and acid-base environments is solved. A high-performance polyurethane lining material has been achieved, which significantly improves service life and iron ore powder selection efficiency.

CN119390927APending Publication Date: 2025-02-07ZHEJIANG AILINGCHUANG MINING INDUSTRY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411492613.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Traditional polyurethane materials are not durable in high wear, high impact and acid-base environments. The lack of magnetic properties makes it difficult to select iron ore powder, and are prone to chemical degradation in high temperature environments and have a short life.

Method used

Nanomagnetic particles forming a core-shell structure by covering the surface of the magnetic ferrite nanoparticles and introducing them into the polyurethane material, a high-performance polyurethane lining material is formed.

Benefits of technology

It significantly improves the wear resistance, impact resistance and chemical corrosion resistance of the material, extends the service life, improves the selection efficiency of iron ore powder, and realizes magnetic separation and recycling, reducing equipment operation costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390927A_ABST
    Figure CN119390927A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a high-performance magnetic polyurethane lining material for an iron ore grinding machine. According to the material, the surface of magnetic ferrite is coated with zirconium oxide to form a core-shell structure, then nano-particles are introduced into a polyurethane formula, and then the nano-particles react with diisocyanate and an arylamine chain extender to prepare the final lining material. The technology is mainly applied to the fields of mining equipment manufacturing and ore processing, and is suitable for high-abrasion and high-impact working environments, such as the iron ore grinding process. In addition, the material also has potential application value in the fields of chemical industry, metallurgy and the like needing high-wear-resistance and chemical corrosion-resistance materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a high-performance composite material, in particular to a magnetic wear-resistant polyurethane material, which is suitable for the inner lining of an iron ore grinding machine. Specifically, the present invention forms a core-shell structure by coating zirconium oxide on the surface of magnetic ferrite nanoparticles, and introduces it into a polyurethane material. The material combines excellent wear resistance, mechanical strength, magnetism and chemical stability, can significantly improve the service life and grinding efficiency of the inner lining of the iron ore grinding machine, and has the functions of iron ore powder selection and material recycling, and is particularly suitable for high-intensity and heavy-wear industrial application environments. Background Art

[0002] Polyurethane materials are widely used in iron ore grinding machine linings due to their good elasticity, wear resistance and chemical stability. However, traditional polyurethane materials are prone to wear and performance degradation under long-term high wear and high impact environments, resulting in frequent equipment maintenance and reduced operating efficiency. In addition, traditional polyurethane materials lack magnetism and cannot effectively separate iron ore powder, making the selection process complicated, reducing the grade of the ore powder, and increasing the difficulty of subsequent processing.

[0003] In recent years, researchers have tried to improve the performance of polyurethane by introducing nanomaterials, especially magnetic ferrite nanoparticles, which have become an important direction for improving the performance of polyurethane composites due to their excellent magnetic and mechanical properties. However, the use of magnetic ferrite alone has some limitations, such as insufficient wear resistance, high temperature resistance and corrosion resistance, and does not perform well in some harsh environments.

[0004] Zirconia is a material with high hardness and strong chemical inertness, and is often used to enhance the wear resistance and chemical stability of materials. Coating zirconium oxide on the surface of magnetic ferrite to form a core-shell structure not only retains the magnetic properties of ferrite, but also significantly improves its wear resistance and chemical stability, thereby effectively improving the shortcomings of existing materials. Therefore, magnetic ferrite / zirconia nanoparticles with core-shell structure can become an ideal reinforcement material for polyurethane lining materials.

[0005] The present invention aims to provide a polyurethane lining material with excellent performance by introducing such core-shell structured nanoparticles, thereby solving the problem of insufficient application of existing polyurethane materials in high-wear, high-impact, and acid-base environments, and further improving the operating efficiency and economic benefits of iron ore grinders. Summary of the invention

[0006] The purpose of the present invention is to provide a high-performance polyurethane lining material, which is particularly suitable for the high wear, high impact and chemical corrosion environment of iron ore grinders. Traditional polyurethane materials are not durable enough under such conditions. At the same time, due to the lack of magnetism, they cannot effectively select iron ore powder during the grinding process, resulting in a decrease in the grade of the ore powder. In addition, in high temperature or acid-base environments, polyurethane materials are prone to chemical degradation and have a short lifespan. In order to solve the above problems, the present invention provides a polyurethane lining material with excellent wear resistance, magnetism, impact resistance and chemical corrosion resistance by introducing magnetic ferrite / zirconia nanoparticles with a core-shell structure, thereby extending its service life, improving the efficiency of iron ore powder selection, reducing material waste, and reducing replacement and maintenance costs.

[0007] In order to achieve the above objectives, the following technical solutions are provided:

[0008] A preparation method of a magnetic wear-resistant polyurethane lining material for an iron ore sand mill:

[0009] (1) 1 gram of magnetic ferrite nanoparticles is dispersed in a zirconium oxychloride solution, wherein the concentration of the zirconium oxychloride solution is 0.1-1M and the volume is 50-200 ml, and a coating reaction is carried out at 50-80° C. for 10-24 hours, and then centrifuged, washed, and dried to obtain ferrite / zirconium oxide nanoparticles;

[0010] (2) 1 gram of the obtained magnetic ferrite / zirconia nanoparticles is subjected to a ring-opening polymerization reaction with 0.5-2 grams of phenyl glycidyl ether under the catalysis of a first catalyst, the reaction temperature being 120-180° C. for 4-8 hours to obtain nanomagnetic particles with surface grafted hydroxyl-terminated polyphenyl glycidyl ether;

[0011] (3) reacting the nanomagnetic particles obtained above, 3-30 g of polymer polyol, diisocyanate, and 0.03-0.3 g of a second catalyst at 80-100° C. to form a prepolymer, wherein the molar ratio of diisocyanate to polymer polyol is 1.1:1;

[0012] (4) After mixing the prepolymer with the aromatic amine chain extender, the prepolymer is pressed into a mold, and a chain extension polymerization reaction is carried out at 90-120° C. to obtain a polyurethane lining material composited with nano-magnetic particles; wherein the molar ratio of the diisocyanate group to the amine group is 1:1.

[0013] Preferably, the first catalyst is aluminum acetylacetonate or its analogs, including zinc acetylacetonate, titanium acetylacetonate, iron acetylacetonate, cobalt acetylacetonate, and the like.

[0014] Preferably, the polyol is polytetramethylene glycol, polypropylene oxide glycol or polyester glycol.

[0015] Preferably, the diisocyanate is toluene diisocyanate, hexamethylene diisocyanate or 4,4'-diphenylmethane diisocyanate.

[0016] Preferably, the second catalyst is dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin diacetate, dimethyltin dicedecanoate, or the like.

[0017] Preferably, the aromatic amine chain extender is 4,4'-diamino-3,3'-dichlorodiphenylmethane, diaminodiphenylmethane, 4,4'-diaminodiphenyl ether, m-phenylenediamine, 1,5-diaminonaphthalene, diaminophenyl sulfide, 3,5-diaminotoluene, 4,4'-diaminobiphenyl, 3,3'-diaminobenzidine, and the like.

[0018] The beneficial effect of the present invention is that the polyurethane lining material provided significantly improves the wear resistance, impact resistance and chemical corrosion resistance of the material by introducing magnetic ferrite / zirconia nanoparticles with a core-shell structure, and prolongs the service life of the material. During the iron ore grinding process, the material can form a protective layer by magnetically adsorbing fine particles of iron ore powder, effectively reducing the direct wear of large particles of ore on the lining. In addition, the detached magnetic ferrite particles can be recycled and reused through magnetic separation, further improving resource utilization and reducing equipment operating costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a sample picture of polyurethane material; Specific implementation methods

[0021] The present invention relates to a preparation method of a magnetic wear-resistant polyurethane lining material, the core of which is to form core-shell structure nanoparticles by coating magnetic ferrite with zirconium oxide, and then combine with the polymer matrix of polyurethane to provide excellent wear resistance, magnetism and chemical corrosion resistance. Zirconium oxide provides a hard shell, which makes the material have good wear resistance and corrosion resistance; while magnetic ferrite gives the material magnetism, which can separate ore powder during iron ore grinding and reduce the direct wear of large particles on the lining.

[0022] The present invention will be further described below with reference to the accompanying drawings and embodiments, and the purpose and effects of the present invention will become more apparent.

[0023] Example 1

[0024] (1) 1 gram of magnetic ferrite nanoparticles is dispersed in a zirconium oxychloride solution having a concentration of 0.1 M and a volume of 50 ml, and a coating reaction is carried out at 50° C. for 10 hours. After centrifugal separation, washing, and drying, ferrite / zirconium oxide nanoparticles are obtained;

[0025] (2) 1 g of the obtained magnetic ferrite / zirconia nanoparticles and 0.5 g of phenyl glycidyl ether were subjected to a ring-opening polymerization reaction under the catalysis of aluminum acetylacetonate at a temperature of 120° C. for 4 hours to obtain nanomagnetic particles with surface grafted hydroxyl-terminated polyphenyl glycidyl ether;

[0026] (3) reacting the obtained nano magnetic particles, 3 g of polytetramethylene glycol, 1.1 g of toluene diisocyanate, and 0.03 g of dibutyltin dilaurate at 80° C. to form a prepolymer, wherein the molar ratio of isocyanate to polyol is 1.1:1;

[0027] (4) After mixing the prepolymer with 4,4'-diamino-3,3'-dichlorodiphenylmethane, the prepolymer is pressed into a mold, and a chain extension polymerization reaction is carried out at 90° C. to obtain a polyurethane lining material composited with nano-magnetic particles, wherein the molar ratio of the isocyanate group to the amine group is 1:1.

[0028] Example 2

[0029] (1) 1 gram of magnetic ferrite nanoparticles is dispersed in a zirconium oxychloride solution having a concentration of 1 M and a volume of 200 ml, and a coating reaction is carried out at 80° C. for 24 hours. After centrifugation, washing, and drying, ferrite / zirconium oxide nanoparticles are obtained;

[0030] (2) 1 g of the obtained magnetic ferrite / zirconia nanoparticles and 2 g of phenyl glycidyl ether were subjected to a ring-opening polymerization reaction under the catalysis of titanium acetylacetonate at a temperature of 180° C. for 8 hours to obtain nanomagnetic particles with surface grafted hydroxyl-terminated polyphenyl glycidyl ether;

[0031] (3) reacting the nanomagnetic particles obtained above, 30 g of polypropylene oxide polyol, 2 g of 4,4'-diphenylmethane diisocyanate, and 0.3 g of dimethyltin dineodecanoate at 100° C. to form a prepolymer, wherein the molar ratio of isocyanate to polyol is 1.1:1;

[0032] (4) After mixing the prepolymer with m-phenylenediamine, the prepolymer is pressed into a mold, and a chain extension polymerization reaction is carried out at 120° C. to obtain a polyurethane lining material composited with nano-magnetic particles, wherein the molar ratio of the isocyanate group to the amine group is 1:1.

[0033] Example 3

[0034] (1) 1 gram of magnetic ferrite nanoparticles is dispersed in a zirconium oxychloride solution having a concentration of 0.5 M and a volume of 100 ml, and a coating reaction is carried out at 60° C. for 12 hours. After centrifugal separation, washing, and drying, ferrite / zirconium oxide nanoparticles are obtained;

[0035] (2) 1 gram of the obtained magnetic ferrite / zirconia nanoparticles and 1 gram of phenyl glycidyl ether were subjected to a ring-opening polymerization reaction under the catalysis of zinc acetylacetonate at a temperature of 140° C. for 5 hours to obtain nanomagnetic particles with surface grafted hydroxyl-terminated polyphenyl glycidyl ether;

[0036] (3) reacting the obtained nanomagnetic particles, 10 g of polyester polyol, 1.2 g of 1,6-hexamethylene diisocyanate, and 0.15 g of dioctyltin dilaurate at 90° C. to form a prepolymer, wherein the molar ratio of isocyanate to polyol is 1.1:1;

[0037] (4) After mixing the prepolymer with 4,4'-diaminodiphenyl ether, the prepolymer is pressed into a mold, and a chain extension polymerization reaction is carried out at 100° C. to obtain a polyurethane lining material composited with nano-magnetic particles, wherein the molar ratio of the isocyanate group to the amine group is 1:1.

[0038] Example 4

[0039] (1) 1 gram of magnetic ferrite nanoparticles is dispersed in a zirconium oxychloride solution having a concentration of 0.8 M and a volume of 150 ml, and a coating reaction is carried out at 70° C. for 20 hours. After centrifugal separation, washing, and drying, ferrite / zirconium oxide nanoparticles are obtained;

[0040] (2) 1 g of the obtained magnetic ferrite / zirconia nanoparticles and 1.5 g of phenyl glycidyl ether were subjected to a ring-opening polymerization reaction under the catalysis of cobalt acetylacetonate at a temperature of 160° C. for 7 hours to obtain nanomagnetic particles with surface grafted hydroxyl-terminated polyphenyl glycidyl ether;

[0041] (3) reacting the obtained nano-magnetic particles, 15 g of polytetramethylene glycol, 1.5 g of toluene diisocyanate, and 0.2 g of dibutyltin diacetate at 95° C. to form a prepolymer, wherein the molar ratio of isocyanate to polyol is 1.1:1;

[0042] (4) After mixing the prepolymer with 4,4'-diaminodiphenyl ether, the mixture is pressed into a mold and subjected to a chain extension polymerization reaction at 110° C. to obtain a polyurethane lining material composited with nano-magnetic particles, wherein the molar ratio of the isocyanate group to the amine group is 1:1.

[0043] Example 5

[0044] (1) 1 gram of magnetic ferrite nanoparticles is dispersed in a zirconium oxychloride solution having a concentration of 0.6 M and a volume of 120 ml, and a coating reaction is carried out at 65° C. for 16 hours. After centrifugation, washing, and drying, ferrite / zirconium oxide nanoparticles are obtained;

[0045] (2) 1 g of the obtained magnetic ferrite / zirconia nanoparticles and 0.7 g of phenyl glycidyl ether were subjected to a ring-opening polymerization reaction under the catalysis of aluminum acetylacetonate at a temperature of 130° C. for 5 hours to obtain nanomagnetic particles with surface grafted hydroxyl-terminated polyphenyl glycidyl ether;

[0046] (3) reacting the obtained nanomagnetic particles, 8 g of polypropylene oxide polyol, 1.4 g of 1,6-hexamethylene diisocyanate, and 0.12 g of dimethyltin dineodecanoate at 85° C. to form a prepolymer, wherein the molar ratio of isocyanate to polyol is 1.1:1;

[0047] (4) After mixing the prepolymer with 3,5-diaminotoluene, the prepolymer is pressed into a mold, and a chain extension polymerization reaction is carried out at 105° C. to obtain a polyurethane lining material composited with nano-magnetic particles, wherein the molar ratio of the isocyanate group to the amine group is 1:1.

[0048] Example 6

[0049] (1) 1 gram of magnetic ferrite nanoparticles is dispersed in a zirconium oxychloride solution having a concentration of 0.3 M and a volume of 80 ml, and a coating reaction is carried out at 55° C. for 14 hours. After centrifugal separation, washing, and drying, ferrite / zirconium oxide nanoparticles are obtained;

[0050] (2) 1 g of the obtained magnetic ferrite / zirconia nanoparticles and 1.2 g of phenyl glycidyl ether were subjected to a ring-opening polymerization reaction under the catalysis of iron acetylacetonate at a temperature of 150° C. for 6 hours to obtain nanomagnetic particles with surface grafted hydroxyl-terminated polyphenyl glycidyl ether;

[0051] (3) reacting the nanomagnetic particles obtained above, 12 g of polyester polyol, 1.3 g of 4,4'-diphenylmethane diisocyanate, and 0.18 g of dibutyltin dilaurate at 88° C. to form a prepolymer, wherein the molar ratio of isocyanate to polyol is 1.1:1;

[0052] (4) After mixing the prepolymer with diaminophenylene sulfide, the mixture is pressed into a mold and subjected to a chain extension polymerization reaction at 115° C. to obtain a polyurethane lining material composited with nano-magnetic particles, wherein the molar ratio of the isocyanate group to the amine group is 1:1.

[0053] Example 7

[0054] (1) 1 gram of magnetic ferrite nanoparticles is dispersed in a zirconium oxychloride solution having a concentration of 0.7 M and a volume of 160 ml, and a coating reaction is carried out at 75° C. for 18 hours. After centrifugal separation, washing, and drying, ferrite / zirconium oxide nanoparticles are obtained;

[0055] (2) 1 g of the obtained magnetic ferrite / zirconia nanoparticles and 1.8 g of phenyl glycidyl ether were subjected to a ring-opening polymerization reaction under the catalysis of cobalt acetylacetonate at a temperature of 170° C. for 7 hours to obtain nanomagnetic particles with surface grafted hydroxyl-terminated polyphenyl glycidyl ether;

[0056] (3) reacting the obtained nano-magnetic particles, 20 g of polytetramethylene glycol, 1.7 g of toluene diisocyanate, and 0.25 g of dibutyltin diacetate at 98° C. to form a prepolymer, wherein the molar ratio of isocyanate to polyol is 1.1:1;

[0057] (4) After mixing the prepolymer with 4,4'-diaminobiphenyl, the prepolymer is pressed into a mold, and a chain extension polymerization reaction is carried out at 118° C. to obtain a polyurethane lining material composited with nano-magnetic particles, wherein the molar ratio of the isocyanate group to the amine group is 1:1.

[0058] Example 8

[0059] (1) 1 gram of magnetic ferrite nanoparticles is dispersed in a zirconium oxychloride solution having a concentration of 0.9 M and a volume of 180 ml, and a coating reaction is carried out at 78° C. for 22 hours. After centrifugation, washing, and drying, ferrite / zirconium oxide nanoparticles are obtained;

[0060] (2) 1 g of the obtained magnetic ferrite / zirconia nanoparticles and 1.4 g of phenyl glycidyl ether were subjected to a ring-opening polymerization reaction under the catalysis of zinc acetylacetonate at a temperature of 175° C. for 7.5 hours to obtain nanomagnetic particles with surface grafted hydroxyl-terminated polyphenyl glycidyl ether;

[0061] (3) reacting the nanomagnetic particles obtained above, 25 g of polypropylene oxide polyol, 1.9 g of 4,4'-diphenylmethane diisocyanate, and 0.28 g of dimethyltin dineodecanoate at 99° C. to form a prepolymer, wherein the molar ratio of isocyanate to polyol is 1.1:1;

[0062] (4) After mixing the prepolymer with 3,3'-diaminobenzidine, the prepolymer is pressed into a mold and subjected to a chain extension polymerization reaction at 119° C. to obtain a polyurethane lining material composited with nano-magnetic particles, wherein the molar ratio of the isocyanate group to the amine group is 1:1.

[0063] The above specific implementation modes are used to explain the present invention rather than to limit the present invention. Any modification and change made to the present invention within the spirit of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.

[0064] Table 1: XRF analysis of zirconia-coated ferroferric oxide nanoparticles

[0065] element percentage(%) iron 50.3 zirconium 21.9 oxygen 26.8 other 0.9

[0066] Table 2: Hardness and wear resistance test table of polyurethane lining materials for example 1 and other iron ore grinding machines

[0067]

Claims

1. A method for preparing a magnetic wear-resistant polyurethane lining material for an iron ore sand mill, characterized in that: The following steps are involved: (1) 1 gram of magnetic ferrite nanoparticles is dispersed in a zirconium oxychloride solution, wherein the concentration of the zirconium oxychloride solution is 0.1-1M and the volume is 50-200 ml, and a coating reaction is carried out at 50-80° C. for 10-24 hours, and then centrifuged, washed, and dried to obtain ferrite / zirconium oxide nanoparticles; (2) 1 gram of the obtained magnetic ferrite / zirconia nanoparticles is subjected to a ring-opening polymerization reaction with 0.5-2 grams of phenyl glycidyl ether under the catalysis of a first catalyst, the reaction temperature being 120-180° C. for 4-8 hours to obtain nanomagnetic particles with surface grafted hydroxyl-terminated polyphenyl glycidyl ether; (3) reacting the nanomagnetic particles obtained above, 3-30 g of polymer polyol, diisocyanate, and 0.03-0.3 g of a second catalyst at 80-100° C. to form a prepolymer, wherein the molar ratio of diisocyanate to polymer polyol is 1.1:1; (4) After mixing the prepolymer with the aromatic amine chain extender, the prepolymer is pressed into a mold, and a chain extension polymerization reaction is carried out at 90-120° C. to obtain a polyurethane lining material composited with nano-magnetic particles; wherein the molar ratio of the diisocyanate group to the amine group is 1:

1.

2. The method for preparing a magnetic wear-resistant polyurethane lining material for an iron ore sand mill according to claim 1, characterized in that: The first catalyst is aluminum acetylacetonate, zinc acetylacetonate, titanium acetylacetonate, iron acetylacetonate, cobalt acetylacetonate, and the like.

3. The method for preparing a magnetic wear-resistant polyurethane lining material for an iron ore sand mill according to claim 1, characterized in that: The polymer polyol is one or more of polytetramethylene glycol, polypropylene oxide glycol or polyester glycol.

4. The method for preparing a magnetic wear-resistant polyurethane lining material for an iron ore sand mill according to claim 1, characterized in that: The diisocyanate is toluene diisocyanate, hexamethylene diisocyanate or 4,4'-diphenylmethane diisocyanate.

5. The method for preparing a magnetic wear-resistant polyurethane lining material for an iron ore sand mill according to claim 1, characterized in that: The second catalyst is dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin diacetate, dimethyltin dicedecanoate, and the like.

6. The method for preparing a magnetic wear-resistant polyurethane lining material for an iron ore sand mill according to claim 1, characterized in that: The aromatic amine chain extender includes 4,4'-diamino-3,3'-dichlorodiphenylmethane, diaminodiphenylmethane, 4,4'-diaminodiphenyl ether, vinylamine, m-phenylenediamine, 1,5-diaminonaphthalene, diaminophenyl sulfide, 3,5-diaminotoluene, 4,4'-diaminobiphenyl, 3,3'-diaminobenzidine and the like.